Pengaruh Asuransi Kesehatan Dan Ekonomi Terhadap Aksesabilitas Layanan Kesehatan Penyandang Disabilitas Di Indonesia - Ririn Nopiah; Heni Wahyuni (Universitas Bengkulu, 2021)
Health insurance is one of social health guarantees programs provided to the society in accessing health services in Indonesia. This program is implemented as a solution of equality problems on health services. This paper aims to analyze effect of health insurance ownership on accessibility health services to people with disabilities who included as vulnerable communities. This research have 1.288 respondents of people with disabilities from Indonesia Family Life Survey that analyzed by multinomial logit regression models. The results show that health insurance ownership of disabilities are not effective enough in accessibility of disabilities health services. To access health service, people with disabilities have main obstacle factor namely physical mobiltity services. Furthermore head of household, chronic disease, transportation costs, and years education variables have significant effect on preventive and curative health services to people with disabilities. Whereas sex and unemployed status significant effect on preventive health services. Keywords : People with Disabilities1, Health Insurance2, Accessibility3, Health Service4